Changes in cerebral oxygen saturation and early postoperative cognitive function after laparoscopic gastrectomy: a comparison with conventional open surgery - Jo, Youn Yi; Kim, Jong Yeop; Lee, Mi Geum; Lee, Seul Gi; Kwak, Hyun Jeong (Korean journal of anesthesiology, 2016)
Laparoscopic gastrectomy requires a reverse-Trendelenburg position and prolonged pneumoperitoneum and it could cause significant changes in cerebral homeostasis and lead to cognitive dysfunction. We compared changes in regional cerebral oxygen saturation (rSO2), early postoperative cognitive function and hemodynamic variables in patients undergoing laparoscopic gastrectomy with those patients that underwent conventional open gastrectomy. Sixty patients were enrolled in this study and the patients were distributed to receive either laparoscopic gastrectomy (laparoscopy group, n = 30) or open conventional gastrectomy (open group, n = 30). rSO2, end-tidal carbon dioxide tension, hemodynamic variables and arterial blood gas analysis were monitored during the operation. The enrolled patients underwent the mini-mental state examination 1 day before and 5 days after surgery for evaluation of early postoperative cognitive function. Compared to baseline value, rSO2 and end-tidal carbon dioxide tension increased significantly in the laparoscopy group after pneumoperitoneum, whereas no change was observed in the open group. No patient experienced cerebral oxygen desaturation or postoperative cognitive dysfunction. Changes in mean arterial pressure over time were significantly different between the groups (P < 0.001). Both laparoscopic and open gastrectomy did not induce cerebral desaturation or early postoperative cognitive dysfunction in patients under desflurane anesthesia. However, rSO2 values during surgery favoured laparoscopic surgery, which was possibly related to increased cerebral blood flow due to increased carbon dioxide tension and the effect of a reverse Trendelenburg position.